Performance evaluation of multi-ONU customers in ethernet passive optical networks - Ciceri, Oscar J.; Astudillo, Carlos A.; da Fonseca, Nelson L. S. (Photonic network communications, 2022)
Resources of Passive Optical Networks (PONs) can be shared by a diverse spectrum of customers such as residential users, business subscribers, mobile network operators, and service providers. A PON customer can rent one or several Optical Network Units (ONUs) from an Infrastructure Service Provider. The ONUs of a customer (multi-ONU customer) can be subject to large spatiotemporal traffic variability, resulting in underutilization of particular ONUs and overutilization of others. The Interleaved Polling with Adaptive Cycle Time with Multi-ONU SLAs support ( MOS-IPACT ) algorithm has been recently proposed to promote the redistribution of unused bandwidth of underloaded ONUs of a multi-ONU customer. This paper introduces an analytical model to evaluate the duration of idle periods in bandwidth usage, as well as a performance evaluation of the MOS-IPACT algorithm in networks with traditional and multi-ONU customers. Numerical results show that the MOS-IPACT algorithm efficiently distributes the excess bandwidth among the ONUs of multi-ONU customers without compromising the bandwidth availability.